2016
DOI: 10.1098/rspb.2016.1558
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphology, adenosine triphosphate (ATP) concentration and swimming velocity: unexpected relationships in a passerine bird

Abstract: The relationship between sperm energetics and sperm function is poorly known, but is central to our understanding of the evolution of sperm traits. The aim of this study was to examine how sperm morphology and ATP content affect sperm swimming velocity in the zebra finch Taeniopygia guttata. We exploited the high inter-male variation in this species and created extra experimental power by increasing the number of individuals with very long or short sperm through artificial selection. We found a pronounced quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 36 publications
3
44
1
Order By: Relevance
“…For many different taxa, the effect of head length on sperm velocity is unclear. Our results are consistent with previous work that found no relationship between velocity and midpiece length but a positive association with head length in zebra finches (Bennison et al, ). However, an interspecific comparison across bird species found no effect of head:flagellum length on velocity but a significant effect of midpiece:flagellum length (Lüpold et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…For many different taxa, the effect of head length on sperm velocity is unclear. Our results are consistent with previous work that found no relationship between velocity and midpiece length but a positive association with head length in zebra finches (Bennison et al, ). However, an interspecific comparison across bird species found no effect of head:flagellum length on velocity but a significant effect of midpiece:flagellum length (Lüpold et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, zebra finches subject to oxidative challenge produce slower sperm with shorter midpieces (Tomáŝek, Albrechtová, Nĕmcová, Opatová, & Albrecht, ). At the same time, however, Bennison, Hemmings, Brookes, Slate, and Birkhead, () found that zebra finch sperm velocity was not correlated with midpiece length nor with ATP content.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, sperm may require more ATP to successfully collide with eggs at low viscosities, and their mitochondria produce ATP less efficiently at high temperatures (Blier et al, ). Unfortunately, the exact energetic benefits of changes in midpiece morphology under warmer conditions are difficult to ascertain, since past studies have found it to have inconsistent relationships with sperm performance (Bennison, Hemmings, Brookes, Slate, & Birkhead, ) and have mostly focused on internal fertilizers with different reproductive biology to Galeolaria (but see Schlegel, Binet, Havenhand, Doyle, & Williamson, ). Nonetheless, shorter or wider midpieces could potentially reflect beneficial rearrangements in the internal organization of mitochondria (Mendonca et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive and functional significance of sperm size variation in birds has received considerable attention in recent years. More generally, sperm length is thought to be an important determinant of sperm swimming speed, an idea with some empirical support at both intra-and interspecific level in passerine birds (Lüpold et al 2009;Bennison et al 2016; but see Kleven et al 2009 andCramer et al 2015). More generally, sperm length is thought to be an important determinant of sperm swimming speed, an idea with some empirical support at both intra-and interspecific level in passerine birds (Lüpold et al 2009;Bennison et al 2016; but see Kleven et al 2009 andCramer et al 2015).…”
mentioning
confidence: 99%